Pengaruh Kewarganegaraan terhadap Status Hukum Perdata dalam Kasus Pernikahan Campuran (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
This study examines the impact of nationality on civil legal status in mixed marriages, particularly in Indonesia and several other countries. Mixed marriages, involving two individuals of different nationalities, often present complex legal issues, especially concerning property ownership, inheritance rights, and the nationality of children. In Indonesia, foreign nationals face various restrictions regarding land and property ownership, and there are temporary provisions for dual nationality for children born from mixed marriages. In a global context, differences between countries following jus soli and jus sanguinis principles also affect the status of children and inheritance rights. This research uses a comparative approach by analyzing civil law regulations in countries such as the United States, the United Kingdom, Japan, and Saudi Arabia. The findings show that Indonesia’s civil law system requires reforms to be more accommodating to the globalization phenomenon and the increasing number of cross-national marriages. Recommendations include harmonizing national regulations with international law, implementing more flexible dual nationality policies, and strengthening protections for the rights of mixed couples in property ownership and inheritance.